Intraoperative Hemodilution and Its Effect on Postoperative Renal Function in Adult Cardiac Surgery Requiring Cardiopulmonary Bypass - Jaiswal, Lokesh Shekher; Pandit, Pramod; Sarraf, Deependra Prasad (Journal of National Heart and Lung Society Nepal, 2024)
Background: Postoperative renal dysfunction after cardiac surgery is associated with morbidity and mortality. Many factors are responsible for renal dysfunction, including intraoperative hemodilution. In this study we have evaluated the effect of guided hemodilution on perioperative renal dysfunction. Methods: All adult patients requiring cardiac surgery under cardiopulmonary bypass were included and their perioperative renal functions were evaluated in terms of blood urea nitrogen, creatinine and creatinine clearance. They were further divided into two groups with <30% (Group A) and > 30% (Group B) rise in creatinine/creatinine clearance to evaluate the effect of hemodilution on postoperative renal function. Results: There was significant difference in preoperative and postoperative renal function between the groups. The preoperative creatinine and creatinine clearance in group A were 0.72±0.2 mg/dL and 97.2±56.5 ml/min respectively and in Group B were 1.1±0.3 mg/dL and 69.7±22.4 ml/min respectively. Postoperative creatinine and creatinine clearance in group A were 0.95±0.3 mg/dL and 78.4±37.7 ml/min respectively and in Group B were 1.35±0.6 mg/dL and 49.4±17.5 ml/min respectively. There were significantly lower mean arterial pressures in Group B (preoperative-72.1±8; postoperative- 71.2±11.4 mmHg) compared to Group A (preoperative- 77.8±10.7; postoperative-72.7±11.0 mmHg). There were significantly more use of packed cells in group B (Intraoperative- 141.2±75.5 ml; total- 297.3±175.4 ml) compared to Group A (intraoperative- 107.1±55.9 ml and total- 150.9±183.4 ml). Conclusion: Optimal hemodilution during cardiopulmonary bypass do not have significant impact on postoperative renal function; however perioperative MAP and perioperative use of PCV are important factors responsible for postoperative rise in serum creatinine and creatinine clearanc.